Factors Affecting Individual Taxpayer Compliance in Pasuruan, Indonesia - Fauziah, Ghea; Sutrisno; Rusydi, Mohammad Khoiru (Accounting Department,, 2024)
Purpose — The goal of this study is to analyze the determinants of compliance intention and taxpayer compliance using constructs derived from the Theory of Planned Behavior, namely religiosity, awareness, and compliance intention, and Social Learning Theory, namely tax knowledge. Design/methodology/approach — This research was conducted on 160 individual taxpayers in the category of entrepreneur and freelancer in Pasuruan city and regency using surveys and Partial Least Squares analysis performed in SmartPLS. Finding — This study finds that compliance intention is determined by religiosity, awareness, and tax knowledge and that compliance intention, religiosity, awareness, and tax knowledge affect taxpayer compliance. Practical Implication — Based on the findings above, the government through the Directorate General of Taxes is advised to use a psychological approach, build a perception that the tax system has been implemented properly, and create transparency to increase taxpayer confidence which can increase compliance intention and the compliance of individual taxpayers. Originality/value — The findings provide additional empirical evidence about tax compliance observed from Social Learning Theory and from the psychological aspect, particularly that the Theory of Planned Behavior can be used to explain taxpayer's compliant behavior. Keywords — taxpayer compliance, the Theory of Planned Behavior, Social Learning Theory Paper type — Positivism paradigm